Suicide Attempts in Epileptics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Causative factors for the high epileptic suicide rate are reported from the Departments of Neurology, University Hospitals of Cleveland and the Johns Hopkins University, Baltimore, MD.